Karyotype analysis and karyological relationships of Turkish Bunium species (Apiaceae) - Çelik, Mustafa; Bağcı, Yavuz; Martin, Esra; Eroğlu, Halil E. (Archives of Biological Sciences, 2020)
Paper description: Chromosome data is valuable and very useful for understanding processes of evolution and speciation. This paper reports the chromosomal data, including karyotype asymmetry, karyological relationships and polyploidy variations, of 10 taxa, 6 of which are given for the first time, 2 have new chromosome numbers, and 2 are in agreement with previous reports. The results of the study provide an important contribution to the cytotaxonomy of Bunium. Abstract: Chromosomal data and karyological relationships provide valuable information about karyotype evolution and speciation. For the genus Bunium, the chromosomal data are limited. In the present study, the chromosomal data of 10 taxa are provided, 6 of which are given for the first time, 2 present new chromosome numbers, and 2 agree with previous reports. Four different chromosome numbers (2n=18, 20, 22 and 40) were detected, and 2n=40 is a new number in the genus Bunium. B. brachyactis is the first polyploid species of the genus with a ploidy level of 4x. The most asymmetric karyotypes are those of B. pinnatifolium and B. sayae. Regarding karyological relationships, B. pinnatifolium forms a monophyletic group by quite different karyological features such as large chromosomes, more submedian chromosomes and the most asymmetric karyotypes. In addition, the other 5 taxa form a strong monophyletic group. B. verruculosum and B. ferulaceum are cytotaxonomically very close species, as are B. sayae and B. elegans var. elegans. The chromosome numbers of 2 Turkish species, B. nudum and B. sivasicum, remain unknown. The presented results provide important contributions to the cytotaxonomy of Bunium. https://doi.org/10.2298/ABS200122014C Received: January 22, 2020; Revised: March 7, 2020; Accepted: April 7, 2020: Published online: April 21, 2020 How to cite this article: Çelik M, Bağcı Y, Martin E, Eroğlu HE. Karyotype analysis and karyological relationships of Turkish Bunium species (Apiaceae). Arch Biol Sci. 2020;72(2):203-9.